1996
DOI: 10.1016/s0304-3959(96)03226-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequential daily relations of sleep, pain intensity, and attention to pain among women with fibromyalgia

Abstract: Fifty women with fibromyalgia syndrome (FS) recorded their sleep quality, pain intensity, and attention to pain for 30 days, using palm-top computers programmed as electronic interviewers. They described their previous night's sleep quality within one-half hour of awakening each day, and at randomly selected times in the morning, afternoon, and evening rated their present pain in 14 regions and attention to pain during the last 30 min. We analyzed the 30-day aggregates cross-sectionally at the across-persons l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
216
1
12

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(245 citation statements)
references
References 38 publications
16
216
1
12
Order By: Relevance
“…Is it even so that poor sleep quality can enhance or even result in pain if persisting for a longer period of time? In a study on pain and sleep in women with fibromyalgia, 32 the authors suggest that poor sleep precedes increased pain, rather than the opposite. On the other hand, in a study in patients with chronic pain conditions, other researchers reported that the onset of sleep disturbances coincided or followed the onset of pain, 13 which suggests that sleep disturbances are secondary to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Is it even so that poor sleep quality can enhance or even result in pain if persisting for a longer period of time? In a study on pain and sleep in women with fibromyalgia, 32 the authors suggest that poor sleep precedes increased pain, rather than the opposite. On the other hand, in a study in patients with chronic pain conditions, other researchers reported that the onset of sleep disturbances coincided or followed the onset of pain, 13 which suggests that sleep disturbances are secondary to pain.…”
Section: Discussionmentioning
confidence: 99%
“…For some, poor sleep becomes a central issue in the course of FMS and poor sleep is inextricably linked with the experience of pain [7,8,9,10]. This association appears to be bi-directional with poor sleep linked to increased reporting of pain, and increased pain linked to poor sleep [8].…”
mentioning
confidence: 99%
“…This association appears to be bi-directional with poor sleep linked to increased reporting of pain, and increased pain linked to poor sleep [8]. Another common complaint is depression [11,12], although less is known about the interaction/s between sleep depression, fatigue, wellbeing and physical functioning in FMS.…”
mentioning
confidence: 99%
See 2 more Smart Citations